Does preoperative weight loss in a specialist medical weight management centre influence postoperative weight loss after bariatric surgery?. Issue 1 (30th September 2022) - Slater, Christopher; Santhosh, Smrithi H.; Ellison, Jodi; Majeed, Waseem; Summers, Lucinda K. M.; Senapati, Siba; Akhtar, Khurshid; Ammori, Basil J.; New, John P.; Syed, Akheel A.
Summary: Weight loss of 5%–10% is advised in medical weight management (MWM) programmes prior to bariatric surgery but it remains to be established whether it influences postoperative weight loss outcomes. We studied postoperative percent total weight loss (%TWL) in 168 patients categorized by preoperative referral weight loss <5% or ≥5% in a UK NHS bariatric centre. Eighty‐six (51.2%) patients achieved sustained referral weight loss <5% (Group A) and 82 (48.8%) ≥5% (Group B). Overall postoperative %TWL in Group A compared with Group B was 30.0% versus 28.3% ( p  = .30) at 12 months and 32.5% versus 29.6% ( p  = .20) at 24 months. There were no significant differences in postoperative %TWL at 12 and 24 months when categorized by procedure (gastric bypass, n  = 106; or sleeve gastrectomy, n  = 62), age or sex. Preoperative weight loss during intensive specialist MWM did not influence postoperative weight loss up to 24 months with gastric bypass or sleeve gastrectomy.